Bone abnormalities and severe arthritis in pachydermoperiostosis. Issue 3 (March 1992) - Cooper, R G; Freemont, A J; Riley, M; Holt, P J; Anderson, D C; Jayson, M I
Abstract : Two patients with pachydermoperiostosis were studied in whom the predominant features at presentation were severe and disabling knee and ankle joint pain in association with distal long bone pain. Analysis of synovial fluid from the knee joints showed non-inflammatory changes. In one patient a bicortical iliac crest bone biopsy specimen, taken after labelling with demeclocycline, showed appositional rates which were increased in cortical bone but reduced in trabecular bone. This mismatching resulted in trabecular osteoporosis, which occurred in association with increased numbers of osteoclasts, findings which suggest differential functional changes affecting the two bony envelopes.